Surgical versus nonsurgical management of pancreatic neuroendocrine tumors: a systematic review and meta-analysis - Khajeh, Elias; Shahrbaf, Mohammadamin; Apostolidis, Leonidas; Michalski, Christoph; Loos, Martin; Mehrabi, Arianeb (Annals of surgical oncology, 2025)
Pancreatic neuroendocrine tumors (PNETs) are a rare type of pancreatic cancer. Surgical resection is the primary curative treatment option, but whether this is the optimal treatment remains debatable. To address this question, we compared surgical versus nonsurgical management of PNETs.